New old stones at Antiochia in Rough Cilicia: A novel city name and a proposed visit by Hadrian and Sabina. Issue 1 (June 2021) - Hoff, Michael; Townsend, Rhys; Howe, Timothy
Abstract: This article considers the evidence of newly discovered inscriptions from Antiochia ad Cragum in western Rough Cilicia and proposes two distinct observations: one, the city had an additional civic name different from that which is most commonly known; and two, the emperor Hadrian and Sabina may have visited the city and region during their journey from Egypt to Athens in 131 CE.